Dynamics of psychological microclimate indices in student groups of medical higher education institutions and their role in development of psychosomatic disorders in students - Zemlyakova, T.D; Antonova, O.V. (Актуальні проблеми транспортної медицини, 2017)
The article presents the dynamics of the psychological microclimate indices in
student groups of medical faculties in the medical higher school (2009-2014-2016 years)
and their role in development of psychosomatic disorders in students with underlying
predisposition to stressful situations. 709 students have participated in studies, 1001
questionnaires have been processed. The obtained data allowed us to estimate the level
of psychological compatibility of students of both faculties (the degree of their “
friendliness”), the authority of group presidents (formal leaders) and true leaders, the
number of outsiders (students who have psychological compatibility with the members
of the group of less than 50%), as well as the number of conflicts, including multiple.
The research results have been used for recreational and corrective method,
representing the methodological guidelines “Autogenic training as an active method of
increasing the psychological working capacity of students and lecturers.” У статті представлено динаміку показників психологічного мікроклімату в студентських групах лікувальних факультетів медичного ВНЗ (2009-2014-2016 рр.) та їх роль у розвитку психосоматичних розладів на фоні схильності до стресових ситуацій. У дослідженнях прийняли участь 709 студентів, оброблено 1001 анкета. Отримані дані дозволили оцінити рівень психологічної сумісності студентів (ступінь їх «дружності»), авторитет старост (формальні лідери) та істинних лідерів, кількість аутсайдерів (студентів, у яких психологічна сумісність з членами групи менш ніж
50%), а також кількість конфліктів, в тому числі множинних. Результати дослідження використані для оздоровчо-корекційного способу у формі методичних вказівок «Аутогене тренування – активний метод підвищення психологічної працездатності студентів та викладачів». В статье представлена динамика
показателей психологического микроклимата в студенческих группах лечебных факультетов медицинского вуза (2009-2014-2016 гг.) и их роль в развитии психосоматических расстройств у студентов на фоне предрасположенности к стрессовым ситуациям. В исследованиях приняли участие 709 студентов, обработана 1001 анкета. Полученные данные позволили оценить уровень психологической совместимости студентов обоих факультетов (степень их «дружности»), авторитет старост (формальные лидеры) и истинных лидеров, количество аутсайдеров (студенты, у которых психологическая совместимость с членами группы менее 50%), а также количество конфликтов, в том числе и множественных. Результаты исследования использованы для оздоровительно-коррекционного способа,
представляющего собой методические указания «Аутогенная тренировка – активный метод повышения психологической работоспособности студентов и преподавателей».